2009
DOI: 10.1210/en.2008-1151
|View full text |Cite
|
Sign up to set email alerts
|

Hormonal Regulation of Prolactin Cell Development in the Fetal Pituitary Gland of the Mouse

Abstract: The developmental process of prolactin (PRL) cells in the fetal pituitary gland was studied in mice. Although PRL cells were hardly detectable in the pituitary gland of intact fetuses, a treatment with 17beta-estradiol (E(2)) in vitro induced a number of PRL cells that varied drastically in number depending on the stage of gestation with a peak at embryonic d 15. This effect was specific to E(2), with epidermal growth factor, insulin, and forskolin failing to induce PRL cells. Although both estrogen receptor (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
10
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(11 citation statements)
references
References 41 publications
1
10
0
Order By: Relevance
“…Our previous studies have revealed that the delayed onset of PRL expression in the mouse pituitary gland is a result of the presence of α‐fetoprotein in the foetal circulation, which binds and inhibits the action of oestrogens, which are strong activators of PRL transcription . Thus far, oestrogens are the only factors able to induce PRL cells in the foetal pituitary gland in mice either in vivo or in vitro . In the present study, we revealed that treatment of foetal pituitary cells with erlotinib and the MAPK kinase inhibitor PD98529 also induced immunocytochemically detectable PRL cells in culture without oestrogen.…”
Section: Discussionsupporting
confidence: 58%
See 1 more Smart Citation
“…Our previous studies have revealed that the delayed onset of PRL expression in the mouse pituitary gland is a result of the presence of α‐fetoprotein in the foetal circulation, which binds and inhibits the action of oestrogens, which are strong activators of PRL transcription . Thus far, oestrogens are the only factors able to induce PRL cells in the foetal pituitary gland in mice either in vivo or in vitro . In the present study, we revealed that treatment of foetal pituitary cells with erlotinib and the MAPK kinase inhibitor PD98529 also induced immunocytochemically detectable PRL cells in culture without oestrogen.…”
Section: Discussionsupporting
confidence: 58%
“…Although pituitary cells other than PRL cells appear in the foetal pituitary gland before parturition, only PRL cells are not detected until after birth in rodents . Our previous studies have revealed that the delayed onset of PRL expression in the mouse pituitary gland is a result of the presence of α‐fetoprotein in the foetal circulation, which binds and inhibits the action of oestrogens, which are strong activators of PRL transcription . Thus far, oestrogens are the only factors able to induce PRL cells in the foetal pituitary gland in mice either in vivo or in vitro .…”
Section: Discussionmentioning
confidence: 99%
“…The lactotrope population was not examined because prolactin expression is estrogen dependent and is not readily detectable until after birth (Ogasawara et al, 2009; Slabaugh et al, 1982). Folliculo-stellate cells are also only detectable post partum, and were not examined in this study (Soji et al, 1997).…”
Section: Resultsmentioning
confidence: 99%
“…2004)), and by the observation, also in mice, that estrogen can induce PRL cells to appear prior to the onset of GH gene expression on day 15 of fetal life (Matsubara et al . 2001, Ogasawara et al . 2009).…”
Section: Discussionmentioning
confidence: 99%